Lateral Patellar Luxation and Ehlers Danlos Syndrome (EDS) in a Dog - Aires, Luiz Paulo Nogueira [UNESP]; Souza, Gislane Vasconcelos de [UNESP]; Faria, Luis Guilherme [UNESP]; Minto, Bruno Watanabe [UNESP]; Jacintho, Ana Paula Prudente; Rossetto, Victor Jose Vieira (Univ Fed Rio Grande Do Sul, 2022)
Background: Ehlers Danlos Syndrome (EDS) is a rare genetic disease characterized by a deficiency in collagen synthesis, which can result in joint laxity. Patellar luxation is one of the main orthopedic conditions that affect the canine knee joint, with limited descriptions of its association with EDS in dogs. The purpose of this report is to describe the surgical management and postoperative evolution of a 1-year-old Chow Chow dog with grade II patellar luxation, tibial valgus and EDS. Case: A 1-year-old Chow Chow dog was referred to the University Veterinary Hospital due to lameness of the left pelvic for 3 months. At the orthopedic examination were verified severe lameness and lateral deviation of the left stifle joint during the ambulation of the animal. Additionally, it was verified bilateral hyperextension of the tibiotarsal joint and grade II patellar luxation of both pelvic limbs with painful hyperextension of the left stifle joint. Radiographic evaluation showed lateral displacement of the patella from both femoral trochlear groove, and a valgus deviation of the proximal left tibial shaft. In addition, it was verified cutaneous hyperextensibility and an extensibility index suggestive of EDS. The animal was submitted to trochlear block resection technique and medial imbrication, followed by corrective tibial osteotomy. Furthermore, skin biopsies of the scapular and lumbar folds were performed during the corrective tibial osteotomy. The samples were sent for histopathological examination, which revealed fragmented and unorganized collagen fibers in the dermis. Histopathological findings were compatible with EDS. The absence of lameness and correct positioning of the patella in the trochlear sulcus were verified in the post-surgical follow-up. Complete bone consolidation of the closing wedge osteotomy to correct the tibial valgus was verified at 90 days postoperatively. Discussion: The clinical signs, cutaneous extensibility index, and histopathological abnormalities in the present case were consistent with EDS. In the present study, this congenital collagen abnormality syndrome may have been a contributing factor of patellar luxation as EDS can result in hypermobility of ligaments and joints, due to metabolic and structural abnormalities of the collagen in connective tissues, and consequently may promote patellar luxation and other orthopedic abnormalities. A variant of EDS in humans has been implicated in the development of skeletal abnormalities such as short stature and bone deformities. This corroborates the possibility that EDS is correlated with valgus angulation of the proximal portion of the tibia in the present case. However, in-depth genetic studies are required to confirm this correlation. Corrective osteotomy in conjunction with block recession sulcoplasty and medial imbrication seem to have enabled patellofemoral stability and alignment of the quadriceps mechanism, ensuring that the patella remained in the trochlear sulcus, even in the presence of EDS. In addition, this syndrome does not seem to affect the surgical outcome of the treatment of patellar luxation associated with closed wedge osteotomy for tibial valgus correction. Medium-term follow-up can be considered excellent in this case report since there was a rapid resolution of lameness and adequate corrective osteotomy healing despite persistent hyperextension of the tibiotarsal joint. Ehlers Danlos Syndrome did not contraindicate the surgical treatment of patellar luxation. However, further studies are needed to assess the influence of the syndrome on long-term patellar luxation. The findings of this case report can help in the diagnosis and treatment of other animals affected by this rare syndrome and associated orthopedic diseases.
Keywords: Patellar luxation; Bone; Collagen diseases